2019
DOI: 10.1155/2019/1346878
|View full text |Cite
|
Sign up to set email alerts
|

2-Allylphenol Reduces IL-1βand TNF-α, Promoting Antinociception through Adenosinergic, Anti-Inflammatory, and Antioxidant Mechanisms

Abstract: 2-Allylphenol (2-AP) is a synthetic phenylpropanoid, structurally related to cardanol, thymol, and ortho-eugenol. Phenylpropanoids are described in the literature as being capable of promoting biological activity. Due to the similarity between 2-AP and other bioactive phenylpropanoids, the present research aims at evaluating the antioxidant, antinociceptive, and anti-inflammatory potential of 2-AP in silico, in vitro, and in vivo. At 30 min prior to the start of in vivo pharmacological testing, administration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…The second phase, related to local inflammation, is more continual and durable and involves the release of pro-inflammatory agents (TNF-α, interleukins, bradykinin, prostaglandins, and serotonin) ( Hunskaar and Hole, 1987 ; Silva et al, 2017 ; Andrade et al, 2020 ). In general, analgesic agents with central action inhibit both phases of the formalin test, such as opioid analgesics, while peripheral analgesic drugs suppress only the second phase ( Aragão Neto et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The second phase, related to local inflammation, is more continual and durable and involves the release of pro-inflammatory agents (TNF-α, interleukins, bradykinin, prostaglandins, and serotonin) ( Hunskaar and Hole, 1987 ; Silva et al, 2017 ; Andrade et al, 2020 ). In general, analgesic agents with central action inhibit both phases of the formalin test, such as opioid analgesics, while peripheral analgesic drugs suppress only the second phase ( Aragão Neto et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that eugenol inhibits pro-inflammatory mediators including interleukins IL-1β and IL-6, tumor necrosis factor-alpha (TNF-α) and prostaglandin E2 (PGE2), inducible expression of oxide nitric synthase (iNOS) and activation of cyclooxygenase-2 (COX-2), nuclear factor kappa B (NF-κB), leukotriene C4 and 5-lipoxygenase (5-LOX). 17–19 …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that eugenol inhibits pro-inammatory mediators including interleukins IL-1b and IL-6, tumor necrosis factoralpha (TNF-a) and prostaglandin E2 (PGE2), inducible expression of oxide nitric synthase (iNOS) and activation of cyclooxygenase-2 (COX-2), nuclear factor kappa B (NF-kB), leukotriene C4 and 5-lipoxygenase (5-LOX). [17][18][19] In this backdrop, we aimed at developing new eugenol derivatives to study their potential anti-inammatory activity. Therefore, we rationally designed eugenol based PPARg agonists, synthesized, puried, analyzed, screened for PPARg binding, and evaluated for in vitro anti-inammatory activity.…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, eugenol can inhibit the generation of superoxide anion in neutrophils, by inhibiting the Raf/MEK/ERK1/2/p47phox-phosphorylation pathway 9 . In parallel, aliphenols such as eugenol have been reported as inhibitors of proinflammatory mediators such as, interleukins IL-1 β and IL-6, tumor necrosis factor alpha (TNF-α) and prostaglandin E2 (PGE2), inducible expression of oxide nitric synthase (iNOS) and expression of cyclooxygenase-2 (COX-2), nuclear factor kappa B (NF-κB), leukotriene C4 and 5-lipoxygenase (5-LOX) [9][10][11][12] .Numerous diseases such as osteoarthritis, Crohn's disease, colon cancer, breast cancer and prostate cancer are associated with the progression of chronic inflammation with activation of pro inflammatory mediators such as interleukins and intracellular enzymes such as COX and LOX [12][13][14][15][16][17][18][19][20][21][22] . The inflammatory process is associated with an increase in the production of prostaglandins.COX is the main enzyme in catalyzing the metabolic conversion of arachidonic acid to prostaglandins, which mediates homeostatic functions in different physiological systems [23][24][25] .…”
mentioning
confidence: 99%
“…According to the literature, eugenol can inhibit the generation of superoxide anion in neutrophils, by inhibiting the Raf/MEK/ERK1/2/p47phox-phosphorylation pathway 9 . In parallel, aliphenols such as eugenol have been reported as inhibitors of proinflammatory mediators such as, interleukins IL-1 β and IL-6, tumor necrosis factor alpha (TNF-α) and prostaglandin E2 (PGE2), inducible expression of oxide nitric synthase (iNOS) and expression of cyclooxygenase-2 (COX-2), nuclear factor kappa B (NF-κB), leukotriene C4 and 5-lipoxygenase (5-LOX) [9][10][11][12] .…”
mentioning
confidence: 99%